Institutional pressure and eco-innovation: The mediating role of green absorptive capacity and strategically environmental orientation among manufacturing SMEs in Egypt - Khalid Mady; Muhammad Abi Sofian Abdul Halim; Khatijah Omar; Reda Shaker Abdelkareem; Mohamed Battour (Cogent Business & Management, 2022)
With the growing concern about climate change, businesses have been under increasing pressure from regulatory agencies and customers to implement proactive environmental practices such as eco-innovation. While environmental pressures have been extensively discussed in the literature as drivers of eco-innovation, empirical evidence on the influence of these pressures on eco-innovation behaviour remains inconsistent. Therefore, the current study essentially aims to investigate the direct effect of institutional pressures, namely, regulation, eco-friendly product demand, and competitive pressure on eco-innovation, coupled with the indirect effect of these pressures by mediating internal drivers of eco-innovation including green absorptive capacity and strategically environmental orientation among manufacturing SMEs in Egypt. Based on a sample of 176 managers and owners of these enterprises, a cross-sectional survey is conducted to collect data related to research constructs. The results of data analysis using Smart-PLS show that all external pressures are not directly associated with eco-innovation. Of the six indirect hypothesized effects, only four indirect effects are supported. The results illustrate that green absorptive capacity mediates the relationship between institutional pressure (eco-friendly product demand and competitive pressure) and eco-innovation. The results also show that strategically environmental orientation mediates the relationship between institutional pressure (regulation and competitive pressure) and eco-innovation. This study provides an in-depth understanding of firms' responses to institutional pressures as well as the notable implications for SMEs managers, policymakers and future researchers.
Keywords: 650; eco-innovation; green absorptive capacity; institutional pressure; strategically environmental orientation